Moderating Effects of Dividend Policy Consistency and ROA on Firm Performance in M&A - Nuansari, Shindy Dwita (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
The occurrence of a positive abnormal return is the dream of every investor in dealing with the decisions taken by the company, because it can provide its own benefits for stakeholders. Therefore, what can create positive abnormality around the announcement of company decision-making, especially Merger and Acquisition (M&A) decisions? To reveal several factors that can create positive abnormal returns around M&A announcements, this study aims to determine the effect of dividend-paying firms on short-term M&A performance which is moderated by the consistency of dividend policy and Return on Assets (ROA) and controlled by size. company using multiple linear regression model. The data used in this research comprises companies in Indonesia that conducted M&A during the period 2002-2021. The total number of observations in this study is 150, and the research employs the Ordinary Least Squares (OLS) technique for analysis. The results of this study indicate that dividend-paying firm has a significant positive effect on short-term M&A performance. The consistency of dividend policy cannot strengthen the positive relationship between dividend-paying firms and short-term M&A performance, but the firm's performance as reflected in ROA, strengthen the positive effect of dividend-paying firms on short-term M&A performance.